Come early morning Bold Films presents a Michel Litvak production ; a Holly Wiersma - Judd, Ashley 1968-; Donovan, Jeffrey 1968-; Nelson, Tim Blake 1964-; Prepon, Laura 1980-; Wilson, Scott 1942-; Keach, Stacy 1941-; Ladd, Diane 1932-; Yorn, Julie 1969-; Wiersma, Holly; Litvak, Michel; Bass, Edward 1956-; Adams, Joey Lauren 1968- (Ivory Music & Video, 2007)
Lucy is a 30-something Southern woman who lives in a small town. She keeps waking up with a hangover and a stranger in her bed. The more she searches for love, the further she gets from it. When Cal moves to town, Lucy is finally able to break free of her old ways and finds the love that she has been looking for.